Detection of serum Candida antigens by enzyme-linked immunosorbent assay and a latex agglutination test with anti-Candida albicans and anti-Candida krusei antibodies. - Fujita, S (1992)
Serum samples from 197 patients with and without candidiasis were assayed for Candida albicans mannan and Candida krusei mannan by an enzyme-linked immunosorbent assay (ELISA) and a latex agglutination test (LA) and for D-arabinitol by the enzymatic fluorometric method. Of the 43 patients positive for C. albicans mannan (> or = 0.2 ng/ml), 34 were infected with C. albicans and 9 were infected with Candida tropicalis. C. krusei mannan (> or = 0.3 ng/ml) was detected in 10 patients infected with Candida parapsilosis, 2 patients infected with Candida guilliermondii, and 1 patient infected with C. krusei. With both anti-C. albicans antibodies and anti-C. krusei antibodies, the sensitivities of ELISA and LA for detection of invasive candidiasis (58 patients) were 74 and 38%, respectively. No false-positive reactions were observed by the ELISA or the LA. The sensitivity and specificity of the D-arabinitol/creatinine ratio (> or = 1.5 mumol/mg) to invasive candidiasis were 50 and 91%, respectively. The ELISA with antibodies against both C. albicans and C. krusei may be useful in diagnosing invasive candidiasis caused by medically important Candida strains excluding Candida glabrata.